2004
DOI: 10.1016/j.febslet.2004.11.079
|View full text |Cite
|
Sign up to set email alerts
|

Presence of syntaxin 1A in secretory granules of chromaffin cells and interaction with chromogranins A and B

Abstract: Syntaxin 1A and synaptotagmin I are key participants of fusion complex formation during exocytotic processes, and syntaxin 1A is known to be present in the plasma membrane. Here, we show the presence of not only synaptotagmin I but also syntaxin 1A in secretory granules of bovine adrenal chromaffin cells by immunogold electron microscopy, and further demonstrate the interaction of these proteins with chromogranins A and B (CGA and CGB), two major proteins of secretory granules. Interaction between chromogranin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…It is highly likely that this Ca 2+ would play key roles in initiating the exocytotic processes by the secretory granules and to a certain extent by synaptic-like vesicles as well, resulting in the secretion of ions and gliotransmitters that participate in the cell-to-cell communication. Moreover, in light of the fact that the SNARE protein syntaxin 1A and synaptotagmin I have been shown to exist in secretory granules of chromaffin cells and interact with chromogranins A and B [86] and that cellubrevin (VAMP3), synaptobrevin 2 and synaptotagmin were shown to colocalize with secretory granule markers in anterior pituitary cells [87], it is highly likely that SNARE proteins also exist in secretory granules of astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly likely that this Ca 2+ would play key roles in initiating the exocytotic processes by the secretory granules and to a certain extent by synaptic-like vesicles as well, resulting in the secretion of ions and gliotransmitters that participate in the cell-to-cell communication. Moreover, in light of the fact that the SNARE protein syntaxin 1A and synaptotagmin I have been shown to exist in secretory granules of chromaffin cells and interact with chromogranins A and B [86] and that cellubrevin (VAMP3), synaptobrevin 2 and synaptotagmin were shown to colocalize with secretory granule markers in anterior pituitary cells [87], it is highly likely that SNARE proteins also exist in secretory granules of astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CgA interacts with several integral membrane proteins of secretory granules, including the inositol 1,4,5-triphosphate receptor/Ca 2ϩ channels to control intracellular Ca 2ϩ release (31)(32)(33)(34)(35), or syntaxin 1A and synaptotagmin I, which par- ticipate in the fusion complex formation during exocytotic events (36). These protein-protein interactions suggest the possibility of communication between the intragranular matrix proteins and the traffic and fusion machineries.…”
Section: Discussionmentioning
confidence: 99%
“…Because one of the primary functions of secretory cells is to store and secrete molecules essential for cellular communication, and the trigger signal for secretion is Ca 2+ (79, 33), the presence of most of cellular Ca 2+ and IP 3 R/Ca 2+ channels along with the highest concentrations of chromogranins in secretory granules highlights the extraordinary efficiency of secretory cells to deal with their complex physiological needs. Moreover, secretory granules also contain Ca 2+ sensor proteins, such as synaptotagmin and syntaxin (98100), which are known to participate in the Ca 2+ ‐initiated membrane fusion and exocytotic processes (101103). These membrane proteins will initiate the fusion process and pave the way for secretion of intragranular contents to the extracellular space and on to the bloodstream (Fig.…”
Section: Physiological Significancementioning
confidence: 99%